2010
DOI: 10.1016/j.joca.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of tenascin-C delays articular cartilage repair in mice

Abstract: This study revealed that cartilage repair in TNKO mice was significantly slower than that in WT mice and that the deficiency of TN-C progressed during cartilage degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Treatment of human articular chondrocytes with TN-C was also shown to accelerate chondrocyte proliferation and play a role in cartilage repair [49]. These findings suggest involvement of TN-C in tissue remodeling that occurs in conjunction with degeneration and repair, which is further emphasized by the delay in articular cartilage repair observed for TN-C-deficient mice [53]. Indeed, we observed a pronounced increase in TN-C release into the joint fluid immediately after surgery in the rat model of OA/joint injury (Figure 8); TN-C levels decreased with time after surgery, indicating the transient expression of TN-C during the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of human articular chondrocytes with TN-C was also shown to accelerate chondrocyte proliferation and play a role in cartilage repair [49]. These findings suggest involvement of TN-C in tissue remodeling that occurs in conjunction with degeneration and repair, which is further emphasized by the delay in articular cartilage repair observed for TN-C-deficient mice [53]. Indeed, we observed a pronounced increase in TN-C release into the joint fluid immediately after surgery in the rat model of OA/joint injury (Figure 8); TN-C levels decreased with time after surgery, indicating the transient expression of TN-C during the repair process.…”
Section: Discussionmentioning
confidence: 99%
“…But in vivo studies in deficient mice (TnC-/-) have revealed a predominant role for TnC in supporting cartilage repair. TnC-/- mice develop cartilage erosion more rapidly after ACL and MCL transection, and cartilage repair is delayed in a focal cartilage defect model [111]. It is possible that the effect of TnC is modified by other factors present in vivo , but additional work is necessary to clarify.…”
Section: Methodsmentioning
confidence: 99%
“…88 However, tenascin-C knockout mice show very minor defects in wound healing exhibiting temporarily reduced fibronectin in the granulation tissue. 89 Impaired tissue repair was observed in these mice after corneal incision injury 90 and articular cartilage damage, 91 implying a possible role for tenascin-C in remodeling during repair. Tamaoki et al 92 showed in a model of myocardial injury that the tenascin-C FBG domain enhanced the migration of myocardial fibroblasts and promoted differentiation into myofibroblasts, in addition to increasing wound contraction.…”
Section: Patterns [Damps]mentioning
confidence: 97%